Assess the reality of the social dimensions in marketing activity Associations Altaaonahalasthlakih in Iraq - fouaad hamoudy alattar (Iraqi Journal for Administrative Sciences, 2024)
The study aims to indicate the social role of the marketing activity of the consumer cooperative societies in Iraq and its social responsibility towards the individual and society, as a sector socially and economically important in the social and economic development of Qatar. Select the number of cooperative societies for the study of a society divided into six Provinces (Baghdad, Babil, Wasit, Najaf, Qadisiyah, Muthanna), while the sample size was selected (80), director of the cooperative. The researcher used a questionnaire form in the Banat from the collection of the sample is composed of two parts, the first of which was devoted to public information, while the second part dealt with questions on the subject of the study. The study found most notably a set of conclusions: that the consumer cooperative societies examined, apply a mixture of the selling and marketing concepts in its dealings with the community, as well as direct marketing activity according to their own circumstances, instead of going on the basis of market conditions. Was to formulate a number of recommendations are consistent with those conclusions, including: the need for the attention of consumer cooperative societies examined, the administration secured the role of social marketing and social responsibility in the exercise